2022
DOI: 10.1111/jnu.12857
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing and witnessing disruptive behaviors toward nurses in COVID‐19 teams, patient safety, and errors in care

Abstract: BackgroundNurse managers and team co‐workers' disruptive behaviors (DBs) are negatively associated with a perceived safe climate. Moreover, DBs are a risk factor for patients' safety. Yet, it remains unknown whether and to what extent these effects were prevalent in COVID‐19 wards and among witnesses of DBs.DesignA cross‐sectional study.MethodsA questionnaire was distributed on social networks and completed by nurses in various Israeli healthcare organizations using snowball sampling between October and Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…1 Healthcare professionals working in an environment with inadequate staff, equipment, and personal protective measures can experience negative emotions, such as tension and anxiety among healthcare professionals, as they struggle to provide care under challenging circumstances. 9 In a previous study, higher disruptive 12 The variable quality of care showed a strong correlation with the dimensions of overall emphasis on patient safety and organizational resources for safety. There was a moderate correlation between quality of care with the dimensions of unit safety norms, senior managers' engagement, unit managers' support, collective learning, psychological safety, and unit recognition and support for safety efforts.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…1 Healthcare professionals working in an environment with inadequate staff, equipment, and personal protective measures can experience negative emotions, such as tension and anxiety among healthcare professionals, as they struggle to provide care under challenging circumstances. 9 In a previous study, higher disruptive 12 The variable quality of care showed a strong correlation with the dimensions of overall emphasis on patient safety and organizational resources for safety. There was a moderate correlation between quality of care with the dimensions of unit safety norms, senior managers' engagement, unit managers' support, collective learning, psychological safety, and unit recognition and support for safety efforts.…”
Section: Discussionmentioning
confidence: 74%
“…Healthcare professionals working in an environment with inadequate staff, equipment, and personal protective measures can experience negative emotions, such as tension and anxiety among healthcare professionals, as they struggle to provide care under challenging circumstances 9 . In a previous study, higher disruptive behaviors of nurse managers and coworkers during the COVID-19 pandemic jeopardized open communication and collaboration among coworkers, particularly among healthcare professionals caring for COVID-19 patients 12 …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The dysfunctional opposite is defined as destructive [ 38 ]. Studies suggest that the ward’s climate of constructive listening may reduce nurses’ exposure to workplace violence [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%